Demand Analysis of Material, Construction Equipment, and Labor on the Superstructure of Type I-Girder Bridge - Tambunan, Reinhard; Aminullah, Akhmad; Sulistyo, Djoko (Universitas Negeri Yogyakarta, 2022)
Infrastructure development is one of the government's main national priority programs to support economic growth and community welfare. One of the issues encountered related to infrastructure development is that the supply chain capacity of material resources, construction equipment, and labor is not yet ideal. The purpose of this study is to analyze the demand for materials, construction equipment, and labor in the construction work of the superstructure of the bridge. This study used secondary data from some bridge construction work packages obtained from the Directorate General of Spatial Planning and Development, Ministry of Public Works. The research step consists of 7 stages. The total number of research samples is 33 consisting of 15 materials (xn), 15 construction equipment (yn), and 3 labor (zn). Of the five bridge construction work packages that meet the research requirements, the type of materials with the largest total demand is cement (x3) 4.904.156,13 kg and asphalt (x5) 578.620,64 kg. Meanwhile, the results of the construction equipment demand analysis show that the heavy equipment with the longest total operational time is dump trucks (y5) 9.395,61 hours and cranes (y12) 2.942,98 hours. From the analysis of demand labor, it is known that the total working time required is workers (z1) 251.753,97 hours, handyman (z2) 151.209,71 hours, and foreman (z3) 59.303,11 hours. In addition, from the five construction work packages, the prestressed concrete I (PCI) girder with the longest size is 45 meters with 35 pieces, while the PCI girder with the shortest size is 20.6 meters with 14 pieces. In terms of needs, the highest number of PCI girders is 42 pieces, and PCI girders with a minimum number of 10 pieces.